Facebook nation total information awareness - Lee, Newton (Springer, 2013)
Facebook as a nation in 2012 would be the third largest country in the world with over 900 million citizens, after China and India. This book portrays the social media ecosystem as a world of increasing Total Information Awareness, which is essentially a civilian version of the controversial Total Information Awareness program unveiled in 2002 by the Defense Advanced Research Projects Agency (DARPA) at the U.S. Department of Defense. Back in the 60's, DARPA initiated and funded the research and development of Advanced Research Projects Agency Network (ARPANET) that went online in 1969. The success of ARPANET gave rise to the global commercial Internet in the 90's and the new generation of Fortune 500 companies today including Amazon.com, Google, eBay, and Yahoo!. Private businesses and the ubiquity of social networks such as Facebook, Google+, Twitter, and YouTube are creating the technologies and infrastructures necessary for the DARPA-proposed Total Information Awareness program.